2010
DOI: 10.5152/akd.2010.094
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of relationship between the D-dimer and ischemia-modified albumin levels with the radiological imaging-based pulmonary embolism severity score in acute pulmonary embolism

Abstract: ÖZETAmaç: İki farklı radyolojik parametre, pulmoner arter obstrüksiyon indeksi (PAOI) ve sağ ventrikül/sol ventrikül oranı (RV/LV) temel alınarak, radyolojik görüntüleme-esaslı pulmoner embolizm şiddet skoru ile D-dimer ve iskemi modifiye albümin (IMA) düzeyleri arasındaki muhtemel ilişkiyi incelemek. Yöntemler: Bu prospektif kohort çalışmasında, acil servise başvuran ve spiral bilgisayarlı tomografi (CT) ile PE kesin tanısı konulan kırk yedi hasta çalış-maya dahil edildi. D-dimer ve IMA düzeyleri sırasıyla im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
1
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 27 publications
1
19
1
2
Order By: Relevance
“…Kazanis et al (13) found higher IMA levels in stable CADs compared to healthy controls and TAS was lower in the CAD group. Besides the role of serum IMA levels in atherosclerotic heart disease (36,37), this marker may be beneficial in determining of diagnosis and mortality in such circumstances as acute mesenteric ischemia, cerebrovascular accidents, endstage renal disease, cardiopulmonary resuscitation, and pulmonary embolism (33,(38)(39)(40)(41). Although serum IMA levels were similar between SCF and control groups, we found a negative correlation between serum IMA levels and TAS in patients with SCF.…”
Section: Discussioncontrasting
confidence: 39%
See 1 more Smart Citation
“…Kazanis et al (13) found higher IMA levels in stable CADs compared to healthy controls and TAS was lower in the CAD group. Besides the role of serum IMA levels in atherosclerotic heart disease (36,37), this marker may be beneficial in determining of diagnosis and mortality in such circumstances as acute mesenteric ischemia, cerebrovascular accidents, endstage renal disease, cardiopulmonary resuscitation, and pulmonary embolism (33,(38)(39)(40)(41). Although serum IMA levels were similar between SCF and control groups, we found a negative correlation between serum IMA levels and TAS in patients with SCF.…”
Section: Discussioncontrasting
confidence: 39%
“…Serum IMA levels have a close relationship with oxidative balance. An inadequate antioxidant supply may lead to increased levels of IMA (17,33). Subsequently, elevated IMA levels may contribute to development and progression of atherosclerotic plaque (34).…”
Section: Discussionmentioning
confidence: 99%
“…The correlation between D-dimer levels and tests for risk stratification in patients with acute PE was reported in 14 studies [11,15,16,18,[22][23][24][25][26][27][28][29][30][31]. Different tools were used across the considered studies for prognostic assessment (Table 4).…”
Section: D-dimer and Determinants Of Prognosismentioning
confidence: 99%
“…37,39,40 Çalışmamızda, Türedi ve ark.nın çalışmasına benzer olarak RV/LV oranı ile PABTOİO arasında, D-dimer düzeyi ile PABTOİO arasında pozitif korelasyon bulunmuştur. 39 Ancak, çalışmamızda, bu çalışmadan farklı olarak D-dimer düzeyi ile RV/LV oranı arasında anlamlı ilişki bulunamamıştır.…”
Section: İstati̇sti̇ksel Anali̇zunclassified